Information Systems – From A Systematic Literature Review to A Modern Vision of a Resilient System - Roberto PAIANO; Luca MAINETTI; Anna Lisa GUIDO (Communications of International Proceedings, 2021)
An information system is highly critical for a company’s long-term viability. The concept of information is used in several contexts and to understand several concepts: from a small software system, to a complex system that manages a company’s information. This confuses people who need to thoroughly understand the concept of information systems (researchers, businesspeople, students, manager etc.). To help resolve matters, this article presents a comprehensive, well-informed examination of the definition and classification of the term information system. The paper highlights the previous research, challenges, current status, and future directions of three key concepts: the concept of data, information, and knowledge very useful for the definition of information system; the concept of information system and all the considerations related to the distinction between the information system and information technology; the classification of the various types of information systems. This review highlights three issues: i) very few authors consider “knowledge” in the definition of information system; ii) there is a great confusion between information system and information technology; ii) there is a no integrated vision that proposes a general classification of information systems. These issues are addressed in the paper presenting a new direction for a modern definition and for an effective design of information system.
Keywords: Information systems; data information knowledge; information system classification; Digital Ecosystem